Diathermy Tonsillectomy Vs conventional Dissection Tonsillectomy - Sharif, Muhammad; Zaman, Javed; Yousaf, Naveed; Iqbal, Kamran (Journal of Postgraduate Medical Institute, 2011)
To compare the conventional metod of tonsillectomy, the dissection snare method with that of the newer procedure, bipolar electrodissection method. We studied 200 cases in two groups, hundred in each. In the first group the patients underwent tonsillectomy by dissection snare method and in the second by electrodissection method. The results of the two groups were studied regarding the time taken in the procedure, blood loss during the procedure, postoperative analgesia required, reactionary hemorrhage, postoperative diet toleration and secondary hemorrhage. We concluded that bipolar electrodissection (diathermy) method is the superior method regarding the time taken during the procedure, the intra operative blood loss was lower and there was no need of ties (ligating the bleeding vessels) in the diathermy method.